2012
DOI: 10.1007/s11695-012-0654-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Changes in Spine and Proximal Femur in Individual Obese Women after Laparoscopic Sleeve Gastrectomy: A Short-Term Study

Abstract: BackgroundThe aim of the study was to establish longitudinal bone changes in obese women after laparoscopic sleeve gastrectomy (LSG).MethodsTwenty-nine women at baseline mean age of 40.41 ± 9.26 years and with mean body mass index (BMI) of 43.07 ± 4.99 kg/m2 were included in a 6-month study. Skeletal status at hip [femoral neck (FN) and total hip (TH)] and spine was assessed at baseline, as well as in 3 and 6 months after surgery. Body size was measured at baseline and follow-up (weight, height, BMI, and waist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 27 publications
4
40
0
3
Order By: Relevance
“…These findings for sleeve gastrectomy are in keeping with a trial of shorter duration in 29 women, which was not included in the above-mentioned systematic review and meta-analysis [61]. Indeed, at 6 months post sleeve gastrectomy, BMD losses relative to pre-surgery values were observed at the hip (-0.059 ± 0.030 g/cm 2 or -5.2%) and femoral neck (-0.072 ± 0.046 g/cm 2 or -7.0%), with a slight but significant decrease at the lumbar spine [61].…”
Section: Effect Of Bariatric Surgery On Bonesupporting
confidence: 59%
See 1 more Smart Citation
“…These findings for sleeve gastrectomy are in keeping with a trial of shorter duration in 29 women, which was not included in the above-mentioned systematic review and meta-analysis [61]. Indeed, at 6 months post sleeve gastrectomy, BMD losses relative to pre-surgery values were observed at the hip (-0.059 ± 0.030 g/cm 2 or -5.2%) and femoral neck (-0.072 ± 0.046 g/cm 2 or -7.0%), with a slight but significant decrease at the lumbar spine [61].…”
Section: Effect Of Bariatric Surgery On Bonesupporting
confidence: 59%
“…The change from pre-surgical values in hip BMD in the RYGB group (nine trials involving RYGB and one trial involving biliopancreatic diversion) was -0.12 g/cm 2 , and in the other surgical group (one trial involving gastric banding and two trials involving sleeve gastrectomy) it was -0.04 g/cm 2 [56]. These findings for sleeve gastrectomy are in keeping with a trial of shorter duration in 29 women, which was not included in the above-mentioned systematic review and meta-analysis [61]. Indeed, at 6 months post sleeve gastrectomy, BMD losses relative to pre-surgery values were observed at the hip (-0.059 ± 0.030 g/cm 2 or -5.2%) and femoral neck (-0.072 ± 0.046 g/cm 2 or -7.0%), with a slight but significant decrease at the lumbar spine [61].…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 72%
“…Moreover, Pluskiewicz et al [1] reported follow up data for only 6 months, which may explain their inability to uncover these changes as we did through a 1-year follow-up period.…”
mentioning
confidence: 66%
“…
We would like to address some of the questions that Dr. Pluskiewicz et al [1] raises in his recent letter. Bone mineral density (BMD) measurements are affected by precision and accuracy errors.
…”
mentioning
confidence: 97%
“…Another prospective, 6-month study [49] examined BMD changes in 29 obese women with a mean BMI of 43 ± 5 kg/m2 after laparoscopic sleeve gastrectomy and found that their BMD decreased by 1.2 % at the lumbar spine, 7.0 % at the femoral neck and 5.2 % at the total hip. All differences from baseline were significant.…”
Section: Effects Of Sleeve Gastrectomy On Bonementioning
confidence: 99%